Physician driven variation in the care of children with spinal muscular atrophy type 1. Issue 5 (29th September 2016) - Oskoui, Maryam; Ng, Pamela; Liben, Stephen; Zielinski, David
Summary: Background: Increasing numbers of families are requesting active supportive management for their child with spinal muscular atrophy type 1 (SMA1), leading to longer survival and greater prevalence of affected children. Strong opinions exist among physicians for and against the provision of care measures prolonging life. Objective: To describe current practice in the care of SMA1 in Canada, and explore the factors underlying inter‐physician variability. Methods: A cross‐sectional survey of Canadian hospital‐based pediatric neurologists and pediatric respirologists was performed in 2015. Odds ratios and 95% confidence intervals were calculated to compare proportions between groups. Results: There was a 54% completion rate (99 physicians). Over half of participants believed that a disease modifying therapy was likely within 10 years. Quebec respirologists were 50 times less likely to offer long‐term non‐invasive ventilation (NIV) than respirologists in other provinces (OR 50.6, 95% CI 2.4–1075.3), and 20 times less likely to discuss tracheostomy with families (OR 20.4, 95% CI 2.0–211.8). High raters of perceived happiness of affected children were more likely to find NIV an acceptable measure for acute (OR 6.7, 95% CI 1.7–26.0) and chronic (OR 13.7, 95% CI 4.0–46.4) respiratory failure and prophylactic use (OR 5.8, 95% CI 2.2–15.6). Conclusion: Physician knowledge, opinions, subjective perception of child happiness, and regional factors, all influence physicians' practices and the shared decision‐making process. Parents may not be informed or offered all the services available to their child. Knowledge translation initiatives are needed to enhance SMA1 care.Pediatr Pulmonol. 2017;52:662–668. © 2016 Wiley Periodicals, Inc.